Molecular basis of SARS-CoV-2 Omicron variant evasion from shared neutralizing antibody response - Patel, Anamika; Kumar, Sanjeev; Lai, Lilin; Chakravarthy, Chennareddy; Valanparambil, Rajesh; Reddy, Elluri Seetharami; Gottimukkala, Kamalvishnu; Bajpai, Prashant; Raju, Dinesh Ravindra; Edara, Venkata Viswanadh; Davis-Gardner, Meredith E; Linderman, Susanne; et al. (bioRxiv, 2022)
A detailed understanding of the molecular features of the neutralizing epitopes developed by viral escape mutants is important for predicting and developing vaccines or therapeutic antibodies against continuously emerging SARS-CoV-2 variants. Here, we report three human monoclonal antibodies (mAbs) generated from COVID-19 recovered individuals during first wave of pandemic in India. These mAbs had publicly shared near germline gene usage and potently neutralized Alpha and Delta, but poorly neutralized Beta and completely failed to neutralize Omicron BA.1 SARS-CoV-2 variants. Structural analysis of these three mAbs in complex with trimeric spike protein showed that all three mAbs are involved in bivalent spike binding with two mAbs targeting class-1 and one targeting class-4 Receptor Binding Domain (RBD) epitope. Comparison of immunogenetic makeup, structure, and function of these three mAbs with our recently reported class-3 RBD binding mAb that potently neutralized all SARS-CoV-2 variants revealed precise antibody footprint, specific molecular interactions associated with the most potent multi-variant binding / neutralization efficacy. This knowledge has timely significance for understanding how a combination of certain mutations affect the binding or neutralization of an antibody and thus have implications for predicting structural features of emerging SARS-CoV-2 escape variants and to develop vaccines or therapeutic antibodies against these.